Pertimbangan Hakim Pengadilan Negeri Kupang Kelas I A dalam Menjatuhkan Pidana Kepada Anak yang Melakukan Tindak Pidana Pencurian Sepeda Motor - E. Nita Juwita; Jonsilas Tanaos (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2023)
This research examines the considerations of judges at the Kupang District Court Class 1A in sentencing children who commit the crime of motorbike theft. The purpose of this research is to find out the consideration of the Kupang District Court Class 1A judge's decision to impose a crime on a child who stole a motorbike. The research method used is descriptive and normative. The results and discussion show that the judge's considerations in imposing a crime on a child include: (1) Juridical considerations, these considerations are the most essential considerations for the Panel of Judges in proving the defendant's actions. (2) Non-juridical considerations, these considerations are considerations regarding the child's motivation for committing theft, the consequences of the child's actions, the child's personal condition, and the aggravating and mitigating circumstances of the child. (3) Consideration of recommendations from the Center for Corrections, this consideration is a very important consideration and influences the criminal decision that will be handed down to the child. (4) Consider the opinion of parents/guardians, this consideration is a consideration that does not have much influence on the criminal decision that will be handed down. Keywords: Criminal Children, Judge's Consideration, Crime of Theft